PEMAHAMAN HEDONISME KONTEMPORER BERDASARKAN STUDI TEOLOGIS DALAM ROMA 6:2 DAN GALATIA 5:19 SERTA IMPLIKASINYA BAGI ORANG KRISTEN MASA KINI - Widya Wahyuni; Yosep Iswanto Padabang (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
Searching for happiness in life is something that is always coveted by everyone, but in seeking and finding it someone needs to be guided and encouraged by the right motivation, so that the happiness obtained can be enjoyed properly, not to satisfy the desires of the flesh which ultimately makes the human being. perish with this world. As taught in the Bible that humans should always live to seek and please God, but in reality what is seen today is, there are so many people who live looking for happiness to satisfy their desires not God's desires. Then what about the life of Christians today? The author uses descriptive qualitative methods, while related to theological studies in relation to the hedonistic lifestyle, the authors relate descriptive qualitative research in the context of phenomenology with qualitative methods that are library research. Which is to analyze the content of meaning contained in a narrative or text, in relation to the Scriptures, the author uses narrative analysis. And in the end it can be concluded that believers should always live according to God's will, which is to do things that show love for God. and abstain from Deeds that originate from the desires of the flesh. and always pursue eternal happiness not temporary happiness taught in hedonism.